2016
DOI: 10.1001/jamapediatrics.2015.3342
|View full text |Cite
|
Sign up to set email alerts
|

Interventions by Health Care Professionals Who Provide Routine Child Health Care to Reduce Tobacco Smoke Exposure in Children

Abstract: IMPORTANCE Reducing child exposure to tobacco smoke is a public health priority. Guidelines recommend that health care professionals in child health settings should address tobacco smoke exposure (TSE) in children. OBJECTIVE To determine the effectiveness of interventions delivered by health care professionals who provide routine child health care in reducing TSE in children. DATA SOURCES A secondary analysis of 57 trials included in a 2014 Cochrane review and a subsequent extended search was performed. Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 64 publications
1
24
0
2
Order By: Relevance
“…Pregnancy and early childhood/infancy offer potential windows for interventions by health care professionals to decrease smoking in mothers and children, and there is some evidence that selected interventions (e.g. maternal postpartum smoking relapse prevention) may be effective . Interventions targeted at young children, prior to the initiation of risky behaviours in adolescence, would be particularly novel.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy and early childhood/infancy offer potential windows for interventions by health care professionals to decrease smoking in mothers and children, and there is some evidence that selected interventions (e.g. maternal postpartum smoking relapse prevention) may be effective . Interventions targeted at young children, prior to the initiation of risky behaviours in adolescence, would be particularly novel.…”
Section: Commentmentioning
confidence: 99%
“…maternal postpartum smoking relapse prevention) may be effective. 34 Interventions targeted at young children, prior to the initiation of risky behaviours in adolescence, would be particularly novel. Animal studies suggest that behavioural and environmental interventions can moderate the effect of epigenetic changes induced by harmful exposures.…”
Section: Commentmentioning
confidence: 99%
“…Secondary analyses of existing review data may be particularly appealing for health policy makers and practitioners interested in quickly identifying effective interventions relevant to their context. For example, secondary analysis on trial data from a subset of studies included in a recently updated Cochrane review [10] was performed on behalf of health services to describe the potential effectiveness of interventions delivered by usual health service staff in reducing child exposure to tobacco smoke [11]. The findings were used to inform local health service practice regarding the type of support provided.…”
Section: The Potential Benefits Of Shared Systematic Review Datamentioning
confidence: 99%
“…Although CEASE has been shown to be an effective intervention [8,10] the study included the first 22 practices that responded to the request to participate in the research study and the sample likely included clinics that were more motivated to implement the CEASE intervention. A review of other interventions to address SHS found less promising results [11]. Provider barriers to assisting parents/family members in quitting smoking include limited time, insufficient understanding of smoking cessation medications, lack of knowledge and access to smoking cessation support resources, coverage for nicotine replacement therapy (NRT) and lack of reimbursement for meaningful cessation counseling of the parent.…”
Section: Introductionmentioning
confidence: 99%